La red ANDI. Una iniciativa latinoamericana de movilización mediática por los derechos de la infancia - Mora Prato, Nora Lisbeth (Revista Española de Desarrollo y Cooperación, 2023)
The media plays an important role in the mobilization of Society, in the awareness of the State and also as a means to denounce and as a source of information for successful social initiatives, mainly after the democratisation process in Brazil that took place in the 1980´s. TV, radio and press take their leading attitude back as essential instruments for transmitting information to both the general public and the people who are responsible for taking decisions. But it is in 1992 when a group of journalists starts a project to build strategies for the social mobilization, taking the media as vehicles for social influence to defence of the childhood rights in Brazil.